Pemberdayaan Ekonomi Smk & Pesantren Melalui Pelatihan Sdm, Tata Kelola Keuangan, Dan Pemasaran Berbasis Teknologi - Aulia Nashuwa; Haykal Redzen Erlangga; Riska Anazwa (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
Economic empowerment within Vocational High Schools (SMK) and Islamic boarding schools (pesantren) represents a strategic effort to enhance institutional self-reliance and competitiveness. This study aims to strengthen the economic independence of vocational and religious education institutions through a Community Service Program (Pengabdian Kepada Masyarakat, PKM) entitled “Economic Empowerment of Vocational Schools and Islamic Boarding Schools through Human Resource Training, Financial Management, and Technology-Based Marketing.” The program was implemented at SMK Insan Kreatif, South Tangerang, using a Participatory Action Research (PAR) approach that emphasizes active involvement of all stakeholders. The training focused on three main areas: developing human resources through the enhancement of soft skills and digital literacy, improving financial management using digital applications, and strengthening marketing strategies through social media and online marketplaces. The results showed a significant improvement in participants’ digital competencies, the ability to create transparent financial reports, and creativity in product promotion. Furthermore, the program fostered stronger synergy between vocational schools and pesantren in developing a technology-based economic ecosystem that is independent, efficient, and sustainable. The findings affirm that collaboration between education and technology plays a strategic role in fostering economic empowerment in the digital era.